Chiral-at-Metal: Iridium(III) Tetrazole Complexes With Proton-Responsive P-OH Groups for CO2 Hydrogenation - Ocansey, Edward; Darkwa, James; Makhubela, Banothile C. E. (Frontiers in Chemistry, 2020)
A rise in atmospheric carbon dioxide levels, following years of burning fossil fuels, has brought about increase in global temperatures and climate change due to the green-house effect. As such, recent efforts aimed at addressing this problem have been directed to the use of carbon dioxide as an inexpensive and non-toxic single carbon source for making chemical products. Herein, we report the use of tetrazolyl complexes as catalysts precursors for hydrogenation of carbon dioxide. Specifically, tetrazolyl compounds bearing phosphorus-sulfur bonds have been synthesized with the view of using these as phosphorus-nitrogen bidentate tetrazolyl ligands that can coordinate to iridium(III) thereby forming heteroatomic five-member complexes. Interestingly, reacting the phosphorus-nitrogen bidentate tetrazolyl ligands with iridium dimer led to serendipitous isolation of chiral-at-metal iridium(III) half-sandwich complexes instead. The complexes were obtained via prior formation non-chiral iridium half-sandwich complexes. The complexes undergo initial phosphorus-sulfur bond heterolysis of the precursor ligands, which then ultimately results in new half-sandwich iridium complexes featuring monodentate phosphine co-ligands with proton responsive functionalities. Conditions necessary to significantly affect the rate of phosphorus-sulfur bond heterolysis in the precursor ligand and the subsequent coordination to iridium have been reported. The complexes served as catalyst precursors and exhibited activity in carbon dioxide and bicarbonate hydrogenation in excellent catalytic activity, at low catalyst loadings, producing concentrated formate solutions exclusively. Catalyst precursors with proton responsive phosphines were found to influence catalytic activity when present as racemates, while ease of dissociation of the ligand from the iridium centre was observed to influence activity in spite of the presence of electron-donating ligands. A test for homogeneity indicated that hydrogenation of carbon dioxide proceeded by homogenous means. Subsequently, the mechanism of the reaction by the iridium catalyst precursors was studied using proton NMR techniques. This revealed that a chiral-at-metal iridium hydride species generated in situ, served as the active catalyst.